2018
DOI: 10.1021/acs.macromol.7b02317
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Polyselenophene Block Copolymer Fiberlike Micelles and Block Co-micelles via Living Crystallization-Driven Self-Assembly

Abstract: We report the formation of near uniform block copolymer fiber-like micelles of controlled length with a crystalline polyselenophene core via the seeded growth process termed living crystallization-driven self-assembly (CDSA). Poly(3-decylselenophene)-blockpoly(dimethylsiloxane) (P3DSe-b-PDMS) forms long, fiber-like micelles in selective solvents. Attempts to control the length of these fibers, by seeded growth following sonication to form the seeds, afforded samples with lengths limited to ca. 300 nm. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 68 publications
0
55
0
Order By: Relevance
“…22 Variants on the seed generation process are also possible. For example, small seeds can be formed by BCP self-assembly under conditions in which homogenous nucleation is favored 23 or, alternatively, in situ by thermal treatment and/or by using conditions of controlled solvency, 24 a method termed "self-seeding" which has its origins in early work on the growth of polymer single crystals. 25 Living CDSA has been extensively developed using BCPs containing poly(ferrocenyldimethylsilane) (PFS) as the crystallizable core-forming block.…”
Section: Introductionmentioning
confidence: 99%
“…22 Variants on the seed generation process are also possible. For example, small seeds can be formed by BCP self-assembly under conditions in which homogenous nucleation is favored 23 or, alternatively, in situ by thermal treatment and/or by using conditions of controlled solvency, 24 a method termed "self-seeding" which has its origins in early work on the growth of polymer single crystals. 25 Living CDSA has been extensively developed using BCPs containing poly(ferrocenyldimethylsilane) (PFS) as the crystallizable core-forming block.…”
Section: Introductionmentioning
confidence: 99%
“…Using this method, Winnik and Manners have successfully prepared 1D cylindrical crystalline micelles with uniform length for various BCPs with PFS as the core‐forming blocks . Preparation of cylindrical micelles via self‐seeding is reported for other BCPs with PCL, P3HT, polyselenophene, OPV, and so forth as the core‐forming block as well. The self‐seeding method can also be applied to prepare cylindrical micelles with a liquid crystalline core …”
Section: Methods For Preparation Of Seed Crystalline Micellesmentioning
confidence: 99%
“…[18][19][20] p-Conjugated polymers have intriguing optical and electronic properties and many examples also exhibit excellent crystallinity.L iving CDSA has been employed to generate fiber-like micelles of controlled length and composition for an umber of BCPs with a p-conjugated polymer block. Examples include poly(thiophene), [13] poly(selenophene), [21] poly(fluorene), [22] oligo(phenylene vinylene) (OPV) [23,24] as the p-conjugated block. [25,26] Recently,s everal reports have shown that fiber-like nanostructures of p-conjugated polymers generated via living CDSA with favorable intermolecular spacing, molecular orientation and dimension are promising candidates for the fabrication of flexible organic electronic and optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…While it is encouraging to see that living CDSA is being developed for an ever increasing range of p-conjugated polymer BCPs, [21][22][23][24][25][26] additional control over the self-assembly process is needed to broaden the scope of potential applications of these nanofibers.F or example,o ne would like to be able not only to control the length of the fibers and the composition of the core-forming block, but also to incorporate divergent functional moieties to meet diverse requirement in different areas. [30] Thus it would be important to be able to introduce functionality along the fibers or at sites along the fibers.I norganic nanoparticles (NPs), including metallic and metal oxide NPs,a nd polymeric NPs are appealing building blocks for the generation of functional materials for various applications.…”
Section: Introductionmentioning
confidence: 99%